Induced Radioactivity in Medical Accelerators - Kalef-Ezra, J. (HNPS Advances in Nuclear Physics, 2012)
Radiation-induced activation of patients and materials in radiotherapy treatment rooms may result in occupational radiation hazards due to in-room induced activity. Induced activation following 18 MV X-ray irradiations was assessed during commissioning and use of a medical linear accelerator at Ioannina University Hospital. Measurements were carried out using hand-held instruments at twenty locations in the accelerator bunker (three portable dose rate meters, a contamination meter were used). Temporal ambient dose rate data fitted with exponential functions and coupled with in situ spectroscopic data were used to characterize the post-irradiation field and develop detailed and practical site-specific work-plans to keep personnel doses secondary to radiotherapy as low as reasonably practical. The application of the suggested work-plans kept occupational exposure at very low levels during the first 2 y of clinical use of such beams.